Working conditions and attitudes towards work: the case of Portuguese youth from Braga - Duque, Eduardo; Durán Vázquez, José F. (Frontiers in Sociology, 2024)
The purpose of this study is to explore the working conditions and attitudes towards work among the youth of Braga, Portugal. Focusing on residents of the Municipality of Braga born between 1990 and 2000, we employed a quantitative approach using a non-probabilistic convenience sampling method, with a sample size of 406 people. The survey, conducted through questionnaires, reveals a complex interplay between the youth's work attitudes and their conditions. Despite the predominance of precarious employment, their work experiences and expectations do not entirely reflect this instability. Our findings suggest a shift in the role of work in the youths' identity compared to previous generations. This shift, common in post-industrial societies, shows that their identity is increasingly tied to the sociability their work enables and other life spheres where they seek fulfilment, as evidenced by how they utilize their earnings from these occupations.